Design and Development of Management Information System on Website-Based Jempol Optical Shop Using the Laravel Framework - Alman Faluti Ashari Alman Faluti Ashari; Rizqi Putri Nourma Budiarti (Universitas Nahdlatul Ulama Surabaya, 2023)
The management of inventory data and reports at the Jempol Optical shop is still manual, starting with the input of goods data relating to glasses, frames, lenses, and other optical accessories data. In addition, the preparation of sales reports is also still manual. It takes a system to collect data on optical goods and to prepare sales reports. This study aims to create a software system that can provide solutions with a website-based management information system using Laravel. The method used in this study uses SDLC (System Development Life Cycle), including literature studies to get references related to the system to be made, needs analysis of the Jempol Optical system to determine system requirements, design of the Jempol Optical system, manufacture of the Jempol Optical system, and system testing of Jempol Optics Website used for black box testing and usability testing. The result of the system created is a management information system with 2 actors (admin and employees) which has 18 features. In black box testing, the system can be used smoothly, and all features can be used according to their functions with a percentage of 100% success. The results of usability testing carried out by shop owners and employees of the Jempol Optical shop, the application is good from the results of tests carried out with a result of 4.2 out of a maximum value of 5. From the test results by giving several statements, it can be concluded that the user agrees with the system that has been made.